Forced migration, arrival in Germany, and first steps toward integration - Herbert Brücker; Nina Rother; Jürgen Schupp; Christian Babka von Gostomski; Axel Böhm; Tanja Fendel; Martin Friedrich; Marco Giesselmann; Yuliya Kosyakova; Martin Kroh; Simon Kühne; Elisabeth Liebau; et al. (DIW Economic Bulletin, 2016)
A new representative survey of a total of 4,500 recently arrived refugees to Germany conducted by the Institute for Employment Research (IAB), the Research Centre of the Federal Office for Migration and Refugees (BAMF-FZ), and the German Socio-Economic Panel (SOEP) at the German Institute for Economic Research (DIW Berlin) has generated an entirely new database for analyzing forced migration and the integration of refugees into German society. The findings we present here are based on the first part of the survey, in which over 2,300 people were interviewed. In addition to the causes of forced migration, the survey captures data on escape routes and educational and vocational biographies. Respondents also answered questions about their values, attitudes, and personality traits, as well as their integration into the German job market and education system. The results show that the threats of war, violence, and persecution were their primary reasons for migration, and that the costs and risks of migration are high. The refugees show extreme heterogeneity in educational backgrounds. The share of respondents who arrived in Germany with vocational or university degrees is low. However, these refugees have high aspirations when it comes to education. And in terms of values, they have more in common with the German population than with the populations of their respective countries of origin. The integration of refugees into the job market and education system has just begun, but Germany's integration policy measures are starting to have a perceptible impact
Keywords: 330